Aktivitas Harian Siamang (Hylobates Syndactylus) Dalam Konservasi Ex-Situ Di Taman Margasatwa Dan Budaya Kinantan Bukittinggi Sumatera Barat - Adelia Hayati Ananta; Defri Yoza; Viny Volcerina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2022)
Gibbons is an endangered species. One of the efforts to prevent the extinction of the gibbons is the ex-situ’s conservation for example zoo. The purpose of this research to determine the daily behavior and the duration of activity of gibbons in habitat at ex-situ in Kinantan Zoo Bukittinggi and to know the difference of frequency daily activities of gibbons. The research was conducted in the month of October-December 2019. The object of this research are six gibbons. The research method was descriptive statistics. The type of this research is observation. Based on the research result, the daily behavior of gibbons at Kinantan Zoo Bukittinggi consists of: the behavior of moving, the behavior of voiced, the behavior of eating, the behavior of social, the behavior of rest, and other behavior (urinate). Total of activity time gibbons obtained during 30 days of observation is 18.319 minutes. The highest behavior shown in the behavior of the resting (12.920 minutes or 70,52%  of total daily activity gibbons). The frequency of daily behavior with a long observation period of 10 hours until 10 hours 30 minutes every day.